Six open doors in the wall of the Frontiers of Science, Technology and Religion - Sequeiros, Leandro; Ferrari Márquez, José Jesús (Razón y fe, 2021)
From an open and pluralistic perspective, an attempt is made to open doors in the frontiers of Science, Technology, and Religion. Many different authors offer interdisciplinary explanations for the emergence of the universe, life, human beings, consciousness, culture, and technology. A recent study by Professor Brian Greene uses the theory of information processing within a Darwinian paradigm to explain global evolution. In dialogue with Greene’s proposals, we try to dialogue with those philosophers and scientists who question some of our positions.
Keywords: Brian Greene; science and religion; evolution